Revalorisation of rapeseed pomace extracts: An in vitro study into its anti-oxidant and DNA protective properties. (15th January 2018) - Pohl, Franziska; Goua, Marie; Bermano, Giovanna; Russell, Wendy R.; Scobbie, Lorraine; Maciel, Patrícia; Kong Thoo Lin, Paul
Highlights: Secondary metabolites analysis in the rapeseed pomace and extracts (95% ethanol) High anti-oxidant/radical scavenging properties of rapeseed pomace ethanol extracts. DNA protective properties of rapeseed pomace extracts against free radical inducer. Potential synergistic effects of phytochemicals present in the RSP extract. RSP, reliable source of natural antioxidants for different food applications. Abstract: Rapeseed pomace (RSP) is a waste product obtained after edible oil production from Brassica napus . Analysis of ubiquitous secondary metabolites in RSP samples (two breeds, harvested in 2012/2014 respectively from North East of Scotland) and their ethanol/water (95:5) Soxhlet extracts were carried out. Soxhlet extraction of the RSP (petroleum ether followed by 95% ethanol) gave a solid extract. LC-MS/MS data of the extracts revealed several secondary metabolites, with Sinapic acid being the most abundant. Strong antioxidant activities of the Soxhlet extracts were confirmed from the results obtained in the FRAP, DPPH and ORAC assays. Furthermore, for the very first time, RSP extracts (13.9 µg/ml) provided complete DNA protection, from oxidative stress induced by AAPH (3.5 mM). Therefore the strong antioxidant and DNA protecting properties demonstrated by the RSP extracts in this study warrants further investigation for their revalorisation and potential use as reliable source of antioxidants in different food applications.